Improvement the Results of the Minimum Competency Assessment (MCA) Literacy and Numeracy Class V SDN Pulogadung District : A Case Study of Fifth Grade Students at SDN Pulogadung District - Ayu ArthaSari Beangelita Napitupulu; Kerdid Simbolon; Candra Ditasona (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2025)
This study is based on the low literacy and numeracy skills of students in Indonesia. This study aims to see the improvement of literacy and numeracy skills possessed by grade V students at SDN Pulogadung. The instrument used in this study is the MCA (Minimum Competency Assessment) test. The approach used in this study is quantitative descriptive with a one group pretest post-test design. Data was collected through the AKM instrument test involving 30 students. The data was analyzed using the Gain test. The results of the study showed that there was an increase in literacy ability of 0.179 and numeracy of 0.379. It can be concluded that literacy skills have increased with low categories while numeracy skills have increased with medium categories.